History and Evolution of the Minimally Invasive Transforaminal Lumbar Interbody Fusion - Prabhu, Michael C.; Jacob, Kevin C.; Patel, Madhav R.; Pawlowski, Hanna; Vanjani, Nisheka N.; Singh, Kern (Neurospine, 2022)
The minimally invasive transforaminal lumbar interbody fusion (MIS-TLIF) is a popular surgical technique for lumbar arthrodesis, widely considered to hold great efficacy while conferring an impressive safety profile through the minimization of soft tissue damage. This elegant approach to lumbar stabilization is the byproduct of several innovations throughout the past century. In 1934, Mixter and Barr’s paper in the New England Journal of Medicine elucidated the role of disc herniation in spinal instability and radiculopathy, prompting surgeons to explore new approaches and instruments to access the disc space. In 1944, Briggs and Milligan published their novel technique, the posterior lumbar interbody fusion (PLIF), involving continuous removal of vertebral bone chips and replacement of the disc with a round bone peg. The following decades witnessed several PLIF modifications, including the addition of long pedicle screws. In 1982, Harms and Rolinger sought to redefine the posterior corridor by approaching the disc space through the intervertebral foramen, establishing the transforaminal lumbar interbody fusion (TLIF). In the 1990s, lumbar spine surgery experienced a paradigm shift, with surgeons placing increased emphasis on tissuesparing minimally invasive techniques. Spurred by this revolution, Foley and Lefkowitz published the novel MIS-TLIF technique in 2002. The MIS-TLIF has demonstrated comparable surgical outcomes to the TLIF, with an improved safety profile. Here, we present a view into the history of the posterior-approach treatment of the discogenic radiculopathy, culminating in the MIS-TLIF. Additionally, we evaluate the hallmark characteristics, technical variability, and reported outcomes of the modern MIS-TLIF and take a brief look at technologies that may define the future MIS-TLIF.